2018
DOI: 10.1111/jopr.12928
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Dental Replica Models Using Photopolymer Materials in Additive Manufacturing: In Vitro Three‐Dimensional Evaluation

Abstract: Although the dental replica models using photopolymer materials did not show better trueness than the conventional stone models, there was no significant difference between the SLA and the stone models. Concerning precision, dental replica models using photopolymer materials presented better results than that of the conventional stone models. In sum, dental replica models using photopolymer materials showed sufficient accuracy for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 29 publications
7
72
0
5
Order By: Relevance
“…Twenty-four studies included reference models as controls in their methodology design [ 6 , 7 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 ]. The controls included were a dental stone cast ( n = 8), a digital STL image of a dental stone cast ( n = 3), typodont digital STL image ( n = 7), typodont ( n = 1), prefabricated resin model digital STL image ( n = 2), patient intraoral scan image (2) or a dry human skull ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four studies included reference models as controls in their methodology design [ 6 , 7 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 ]. The controls included were a dental stone cast ( n = 8), a digital STL image of a dental stone cast ( n = 3), typodont digital STL image ( n = 7), typodont ( n = 1), prefabricated resin model digital STL image ( n = 2), patient intraoral scan image (2) or a dry human skull ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies investigated SLA ( n = 20), MJ ( n = 11), DLP ( n = 9) and, to a lesser extent, FFF ( n = 6), BJ ( n = 2) and CLIP ( n = 1). With regards to printing parameters, one study reported following the manufacturers’ recommendations [ 6 ], while others explicitly detailed the printing parameters used [ 4 , 19 , 36 , 37 , 38 , 42 , 43 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 55 , 56 , 57 ]. In contrast, the remainder of the studies did not provide clear details regarding the printing parameters used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of this technology is that the 3D objects grow continuously without interruption by controlling the oxygen flux. Jin et al studied the accuracy of dental replica models produced by SLA and PolyJet techniques compared with the conventional method. They measured the trueness and the precision of printed models with conventional stone models.…”
mentioning
confidence: 99%
“…Jin и соавт. [11] в своем исследовании не выявили статистически значимой разницы в размерной точности гипсовых моделей челюстей и моделей, полученных методом стереолитографии, но пришли к выводу, что модели, изготовленные из фотополимерных материалов с помощью 3Dпринтера, могут быть рекомендованы для клинического использования.…”
Section: таблица 1 результаты измерения медианы расстояний между вирunclassified